THE EFFECT OF DISPLACEMENT VENTILATION ON THERMAL COMFORT AND INDOOR AIR QUALITY IN ITB'S ENGINEERING PHYSICS DEPARTMENTâS MULTIMEDIA ROOM - Zahra Amalia Putri, Vania
Humans spend 87% of their time indoors, making indoor environmental quality (IEQ) crucial for comfort and health. IEQ is determined by four main factors: lighting, acoustics, thermal conditions, and indoor air quality. In Indonesia, a tropical country with relatively high temperatures and humidity, people tend to prefer indoor activities. This preference often leads to poor indoor air quality. The primary cause of deteriorating indoor air quality is insufficient ventilation, highlighting the importance of selecting an appropriate ventilation system. Numerous studies have shown that displacement ventilation can improve not only thermal comfort but also indoor air quality. This study aims to identify the impact of using displacement ventilation on thermal comfort and indoor air quality, particularly in tropical regions. Data were collected using both objective and subjective methods. Objective measurements included data on air temperature, air velocity, relative humidity, and carbon dioxide levels. For subjective measurements, seven respondents were involved in a survey assessing thermal sensations in a room with displacement ventilation. Assuming the multimedia room as a computer lab and office that meets infection risk management standards, this study varied the fresh air flow rate into the room. The results indicate that the use of displacement ventilation with varying fresh air flow rates creates a temperature difference between the head and feet that does not exceed 2°C. The indoor air temperature remains within the thermal comfort zone, with air velocity at the head below 0.25 m/s and at the feet ranging from 0.08 to 0.27 m/s. Carbon dioxide levels were recorded within the range of 314 to 465 ppm. According to the survey, respondents felt comfortable in 78% variations of blower speed frequency. However, some respondents reported symptoms of Sick Building Syndrome (SBS).